Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ani10020295
|View full text |Cite
|
Sign up to set email alerts
|

KA-1002, a Novel Lysophosphatidic Acid Signaling Antagonist, Alleviates Bovine Tracheal Cell Disruption and Inflammation

Abstract: The industrial livestock environment can cause stress and weakened immunity in cattle, leading to microbial infections which reduce productivity. As such, there is a need for an effective therapeutic agent that can alleviate uncontrolled destructive respiratory inflammation. We found that lysophosphatidic acid (LPA), a potent endogenous stress-induced inflammatory agent, causes respiratory tissue damage and triggers inflammation in bovine bronchial cells. LPA also inflames pulmonary bovine blood vessel cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These transcriptome results suggest that LPA induce suppression of T cell responses and upregulation of innate immune cells-mediated inflammation. Multiple previous reports [12][13][14] support our hypothesis. Mathew D et al showed that LPA suppresses CD8+T cell cytotoxicity function via disruption of early TCR signaling [13].…”
Section: Selecting Distinguished Genes Between Lpa-treated and Lpa Psupporting
confidence: 89%
See 4 more Smart Citations
“…These transcriptome results suggest that LPA induce suppression of T cell responses and upregulation of innate immune cells-mediated inflammation. Multiple previous reports [12][13][14] support our hypothesis. Mathew D et al showed that LPA suppresses CD8+T cell cytotoxicity function via disruption of early TCR signaling [13].…”
Section: Selecting Distinguished Genes Between Lpa-treated and Lpa Psupporting
confidence: 89%
“…For example, LPA strongly induced inflammatory angiogenesis and the production of inflammatory cytokine [14]. Furthermore, we found a novel LPA-antagonistic molecule, KA-1002 [13], which strongly alleviated LPA-induced inflammatory responses from bovine respiratory cells and blood endothelial cells. However, we did not understand the effect of the LPA antagonistic molecule, KA-1002 on swine cells.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations